BN-Al-ZrB2-TiC composite material, preparation method thereof and application of BN-Al-ZrB2-TiC composite material in PcBN cutter
By adopting the preparation method of BN-Al-ZrB2-TiC composite material, the problem of single bonding agent system in PcBN tools is solved, and more efficient cutting performance in high-strength or high-hardness material processing is achieved. Lower production costs.
Patent Information
- Application Number
- CN202411700952.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The binding agent system in PcBN tools is relatively single, with excess hardness and insufficient toughness, which leads to poor performance when processing high-strength or high-hardness materials, requiring frequent replacement, which increases production costs and downtime.
Using BN-Al-ZrB2-TiC composite material, ball milling, drying, sieving and segmentation are performed by first mixing zirconium boride with titanium carbide, followed by second mixing with cubic boron nitride, aluminum powder and solvent. Pressurized sintering gives a composite material with improved toughness and increased hardness.
It has achieved great advantages in cutting processing such as high-speed cutting, and has high efficiency and environmental protection characteristics. It is a high-strength, high-strength, tough, PcBN tool composite material.
Smart Images

Figure CN119430953A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a BN-Al-ZrB2-TiC composite material and a preparation method thereof, and application in a PcBN cutting tool. Background Art
[0002] With the continuous development of modern technology and heavy industry, more and more high-strength, high-hardness and difficult-to-process materials are widely used in various industrial production. Although these materials have excellent performance, they also bring many challenges during the processing. Therefore, in this industrial context, it is particularly important to choose the right tool. The correct tool selection can achieve a higher material removal rate and make the processing process more efficient. For traditional cutting tools, there are often defects such as poor wear resistance, low thermal stability, and limited cutting speed during the processing process. Therefore, they perform poorly when processing high-strength or high-hardness materials, and often need to be replaced frequently, increasing production costs and downtime. At the same time, traditional tools are highly dependent on cutting fluids, which also brings challenges in terms of environmental protection and cost control.
[0003] Cubic boron nitride (cBN) is a material second only to diamond in hardness and wear resistance, and has better thermal stability and chemical stability than diamond. Polycrystalline cubic boron nitride (PcBN) is prepared under high temperature and high pressure by combining cubic boron nitride (cBN) with an appropriate amount of binder. As a new type of tool material, PcBN tools have become the most promising tool material after artificial diamonds due to their own advantages such as high hardness, high wear resistance, high toughness and thermal stability. The research and development of PcBN tools is one of the keys to achieving high-speed and high-precision cutting of difficult-to-process materials. However, at present, PcBN tools have defects such as a relatively single binder system, excessive hardness and insufficient toughness. Summary of the invention
[0004] The purpose of the present invention is to provide a BN-Al-ZrB2-TiC composite material and a preparation method thereof and application in a PcBN tool, so as to solve the problem that the binder system in the PcBN tool is relatively single, the hardness is sufficient but the toughness is insufficient.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a BN-Al-ZrB2-TiC composite material, comprising the following steps:
[0007] Performing a first mixing of zirconium boride and titanium carbide to obtain a first mixed material;
[0008] The first mixed material is mixed with cubic boron nitride, aluminum powder and solvent for a second time, and then ball-milled, dried and sieved in sequence to obtain a second mixed material;
[0009] The second mixed material is subjected to staged pressure sintering to obtain a BN-Al-ZrB2-TiC composite material.
[0010] Preferably, the molar ratio of the zirconium boride to titanium carbide is 1:0.6-1.4, and the first mixing time is 15-45 minutes.
[0011] Preferably, the mass ratio of the cubic boron nitride, the aluminum powder and the first mixed material is 50-80:6:14-44.
[0012] Preferably, the rotation speed of the ball mill is 80 to 200 r / min, the time is 360 to 840 min, and the ball-to-material ratio is 2 to 5:1.
[0013] Preferably, the drying temperature is 60-100° C., and the drying time is 16-30 hours; and the mesh size of the sieve used for sieving is 100-400 meshes.
[0014] Preferably, a six-sided top press is used to carry out the segmented pressure sintering; the pressure applied by the six-sided top press is 4 to 7 GPa.
[0015] Preferably, the staged pressure sintering includes: the first stage: the temperature is 900-1400°C, the holding time is 1-3 minutes, and the heating rate from room temperature to the temperature of the first stage is 300-500°C / min; the second stage: the temperature is 1500-2000°C, the holding time is 5-10 minutes, and the heating rate from the temperature of the first stage to the temperature of the second stage is 300-500°C / min.
[0016] The present invention provides a BN-Al-ZrB2-TiC composite material prepared by the preparation method described in the above technical solution.
[0017] The present invention provides the application of the BN-Al-ZrB2-TiC composite material described in the above technical solution in a PcBN cutting tool.
[0018] The invention provides a preparation method of a BN-Al-ZrB2-TiC composite material. The method adopts cBN powder, Al powder, ZrB2 powder and TiC powder as raw materials, takes cBN as a matrix, and uses Al, ZrB2 and TiC as bonding phases, thereby solving the problem of a single bonding agent system. During the sintering process under high temperature and high pressure, the raw materials react with each other, and the bonding phase is evenly distributed between cubic boron nitride particles. Al, as a metal, has good toughness, and its addition as a bonding agent is beneficial to improving the problem of excessive hardness but insufficient toughness of a cutting tool. Secondly, during the sintering process, Al gradually melts and enters the gaps between particles to fill the gaps and promote the densification of the material. At the same time, it wets the surface of cBN particles, activates them, and promotes the reaction. The AlN generated by the reaction inhibits the phase transformation of cBN to hBN. ZrB2-TiC is a reinforcing phase. ZrB2 and TiC have high strength, high hardness and high wear resistance. The reinforcing phase ZrB2 partially reacts with TiC. On the one hand, the reaction generates fine titanium boride and zirconium carbide. The particles are smaller and more evenly distributed, which can better fill the pores between the composite material particles. At the same time, the smaller grains can improve the hardness and bending strength of the material. On the other hand, some solid solutions will be generated to promote the sintering and densification of ceramic materials, refine the grain size, and improve the strength, hardness and wear resistance of the material. The mechanical bonding of traditional binders makes the tool prone to chipping and cracking during processing. Therefore, the BN-Al-ZrB2-TiC composite material of the present invention has great advantages in cutting processes such as high-speed cutting, and also has the characteristics of high efficiency and environmental protection, and is a high-strength and high-toughness PcBN tool composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 XRD results of the BN-Al-ZrB2-TiC composite material in Example 2;
[0020] Figure 2 is the SEM image of the sintered raw material after ball milling in Example 2;
[0021] Figure 3 The surface morphology of the BN-Al-ZrB2-TiC composite material prepared in Example 1;
[0022] Figure 4 The fracture morphology of the BN-Al-ZrB2-TiC composite material prepared in Example 2;
[0023] Figure 5 is the flexural strength curve of the BN-Al-ZrB2-TiC composite material prepared in Example 3;
[0024] Figure 6 This is the Vickers hardness curve of the BN-Al-ZrB2-TiC composite material prepared in Example 3. DETAILED DESCRIPTION
[0025] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0026] The present invention provides a method for preparing a BN-Al-ZrB2-TiC composite material, comprising the following steps:
[0027] Performing a first mixing of zirconium boride and titanium carbide to obtain a first mixed material;
[0028] The first mixed material is mixed with cubic boron nitride, aluminum powder and solvent for a second time, and then ball-milled, dried and sieved in sequence to obtain a second mixed material;
[0029] The second mixed material is subjected to staged pressure sintering to obtain a BN-Al-ZrB2-TiC composite material.
[0030] In the present invention, zirconium boride and titanium carbide are first mixed to obtain a first mixed material.
[0031] In the present invention, the molar ratio of zirconium boride to titanium carbide is preferably 1:0.6-1.4, more preferably 1:0.8-1.2, and more preferably 1:0.9-1; the first mixing time is preferably 15-45 min, more preferably 20-40 min, and more preferably 25-30 min.
[0032] After obtaining the first mixed material, the present invention secondly mixes the first mixed material with cubic boron nitride, aluminum powder and solvent, and then performs ball milling, drying and sieving in sequence to obtain a second mixed material.
[0033] In the present invention, the particle sizes of the zirconium boride, titanium carbide, cubic boron nitride and aluminum powder are all micrometer-level.
[0034] In the present invention, the solvent is preferably anhydrous ethanol; the present invention has no special limitation on the amount of the solvent, and the amount can be adjusted according to actual needs to ensure that the grinding is completed.
[0035] In the present invention, the mass ratio of the cubic boron nitride, the aluminum powder and the first mixed material is preferably 50-80:6:14-44, more preferably 55-75:6:19-39, and more preferably 60-70:6:24-34.
[0036] The present invention has no particular limitation on the second mixing, and the materials may be mixed uniformly according to a process well known in the art.
[0037] In the present invention, the rotation speed of the ball mill is preferably 80-200 r / min, more preferably 120-160 r / min, more preferably 140-150 r / min; the time is preferably 360-840 min, more preferably 480-720 min, more preferably 540-640 min; the ball-to-material ratio is preferably 2-5:1, more preferably 2.5-4.5:1, more preferably 3-4:1.
[0038] In the present invention, the drying temperature is preferably 60-100°C, more preferably 70-90°C, and more preferably 75-80°C; the drying time is preferably 16-30h, more preferably 18-28h, and more preferably 24-26h; the mesh size of the sieve used for sieving is preferably 100-400 mesh, more preferably 150-350 mesh, and more preferably 200-300 mesh.
[0039] After obtaining the second mixed material, the present invention performs segmented pressure sintering on the second mixed material to obtain a BN-Al-ZrB2-TiC composite material.
[0040] The present invention preferably uses a six-sided top press to perform the segmented pressure sintering; the pressure applied by the six-sided top press is preferably 4 to 7 GPa, more preferably 4.5 to 6 GPa, and even more preferably 5 to 5.5 GPa.
[0041] In the present invention, the staged pressure sintering preferably includes: the first stage: the temperature is 900-1400°C, the holding time is 1-3 minutes, and the heating rate from room temperature to the temperature of the first stage is 300-500°C / min; the second stage: the temperature is 1500-2000°C, the holding time is 5-10 minutes, and the heating rate from the temperature of the first stage to the temperature of the second stage is 300-500°C / min.
[0042] In the present invention, the temperature of the first stage is more preferably 1000-1300°C, and further preferably 1100-1200°C; the heating rate from room temperature to the temperature of the first stage is more preferably 350-450°C / min, and further preferably 380-400°C / min; the holding time of the first stage is more preferably 1.5-2.5min, and further preferably 1.8-2.0min.
[0043] The temperature of the second stage is more preferably 1500-1800°C, and further preferably 1550-1600°C; the heating rate from the temperature of the first stage to the temperature of the second stage is more preferably 350-450°C / min, and further preferably 380-400°C / min; the insulation time of the second stage is more preferably 6-9min, and further preferably 7-8min.
[0044] After completing the segmented pressure sintering, the present invention is naturally cooled to room temperature to obtain a BN-Al-ZrB2-TiC composite material.
[0045] The present invention provides a BN-Al-ZrB2-TiC composite material prepared by the preparation method described in the above technical solution.
[0046] The present invention provides the application of the BN-Al-ZrB2-TiC composite material in the PcBN tool. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] In the following examples, the particle sizes of zirconium boride, titanium carbide, cubic boron nitride and aluminum powder are 1-3 μm, 1-2 μm, 2-4 μm and 1 μm, respectively.
[0049] Example 1
[0050] 1) Weigh 24 g of zirconium boride and titanium carbide powder in a molar ratio of 1:1 and mix them for 30 min to obtain a mixed powder;
[0051] 2) 70 g of cubic boron nitride powder, 6 g of aluminum powder, and 24 g of mixed powder of zirconium boride and titanium carbide were added to a ball mill, and 150 g of anhydrous ethanol was added. The mixture was milled using a planetary ball mill with a ball-to-material ratio of 3:1, a rotation speed of 150 r / min, and a mixing time of 640 min to obtain a sintering raw material;
[0052] 3) The sintered raw materials were vacuum dried at 80°C for 24 hours, and the dried sintered raw materials were passed through a 300-mesh sieve;
[0053] 4) The dried sintering raw materials are loaded into a graphite mold, and then sintered using a six-sided top press. While gradually increasing the pressure, the temperature is increased from room temperature to 1200°C at a rate of 400°C / min and kept for 2 minutes, and then increased to 1600°C at a rate of 400°C / min. At this time, the maximum sintering pressure of 5.5 GPa is maintained for 8 minutes, and then naturally cooled to room temperature to obtain a BN-Al-ZrB2-TiC composite material.
[0054] Example 2
[0055] 1) Weigh 24 g of zirconium boride and titanium carbide powder in a molar ratio of 1:1 and mix them for 30 min to obtain a mixed powder;
[0056] 2) 70 g of cubic boron nitride powder, 6 g of aluminum powder, and 24 g of mixed powder of zirconium boride and titanium carbide were added to a ball mill, and 150 g of anhydrous ethanol was added. The mixture was milled using a planetary ball mill with a ball-to-material ratio of 3:1, a rotation speed of 150 r / min, and a mixing time of 640 min to obtain a sintering raw material;
[0057] 3) The sintered raw materials were vacuum dried at 80°C for 24 hours, and the dried sintered raw materials were passed through a 300-mesh sieve;
[0058] 4) The dried sintering raw materials are loaded into a graphite mold, and then sintered using a six-sided top press. While gradually increasing the pressure, the temperature is increased from room temperature to 1200°C at a rate of 400°C / min and kept for 2 minutes, and then increased to 1500°C at a rate of 400°C / min. At this time, the maximum sintering pressure of 5.5 GPa is maintained for 8 minutes, and then naturally cooled to room temperature to obtain a BN-Al-ZrB2-TiC composite material.
[0059] Example 3
[0060] 1) Weigh 24 g of zirconium boride and titanium carbide powder in a molar ratio of 1:1 and mix them for 30 min to obtain a mixed powder;
[0061] 2) 70 g of cubic boron nitride powder, 6 g of aluminum powder, and 24 g of mixed powder of zirconium boride and titanium carbide were added to a ball mill, and 150 g of anhydrous ethanol was added. The mixture was milled using a planetary ball mill with a ball-to-material ratio of 3:1, a rotation speed of 150 r / min, and a mixing time of 640 min to obtain a sintering raw material;
[0062] 3) The sintered raw materials were vacuum dried at 80°C for 24 hours, and the dried sintered raw materials were passed through a 300-mesh sieve;
[0063] 4) The dried sintering raw materials are loaded into a graphite mold, and then sintered using a six-sided top press. While gradually increasing the pressure, the temperature is increased from room temperature to 1200°C at a rate of 400°C / min and kept for 2 minutes, and then increased to 1550°C at a rate of 400°C / min. At this time, the maximum sintering pressure of 5 GPa is maintained for 8 minutes, and then naturally cooled to room temperature to obtain a BN-Al-ZrB2-TiC composite material.
[0064] Example 4
[0065] 1) Weigh 24 g of zirconium boride and titanium carbide powder in a molar ratio of 1:0.8 and mix them for 30 min to obtain a mixed powder;
[0066] 2) 70 g of cubic boron nitride powder, 6 g of aluminum powder, and 24 g of mixed powder of zirconium boride and titanium carbide were added to a ball mill, and 150 g of anhydrous ethanol was added. The mixture was milled using a planetary ball mill with a ball-to-material ratio of 3:1, a rotation speed of 150 r / min, and a mixing time of 640 min to obtain a sintering raw material;
[0067] 3) The sintered raw materials were vacuum dried at 80°C for 24 hours, and the dried sintered raw materials were passed through a 300-mesh sieve;
[0068] 4) The dried sintering raw materials are loaded into a graphite mold, and then sintered using a six-sided top press. While gradually increasing the pressure, the temperature is increased from room temperature to 1100°C at a rate of 400°C / min and kept for 2 minutes, and then increased to 1600°C at a rate of 400°C / min. At this time, the maximum sintering pressure of 5.5 GPa is maintained for 8 minutes, and then naturally cooled to room temperature to obtain a BN-Al-ZrB2-TiC composite material.
[0069] Example 5
[0070] 1) Weigh 24 g of zirconium boride and titanium carbide powder in a molar ratio of 1:0.8 and mix them for 30 min to obtain a mixed powder;
[0071] 2) 70 g of cubic boron nitride powder, 6 g of aluminum powder, and 24 g of mixed powder of zirconium boride and titanium carbide were added to a ball mill, and 150 g of anhydrous ethanol was added. The mixture was milled using a planetary ball mill with a ball-to-material ratio of 3:1, a rotation speed of 150 r / min, and a mixing time of 640 min to obtain a sintering raw material;
[0072] 3) The sintered raw materials were vacuum dried at 80°C for 16 hours, and the dried sintered raw materials were passed through a 300-mesh sieve;
[0073] 4) The dried sintering raw materials are loaded into a graphite mold, and then sintered using a six-sided top press. While gradually increasing the pressure, the temperature is increased from room temperature to 1200°C at a rate of 350°C / min and kept for 3 minutes, and then increased to 1600°C at a rate of 350°C / min. At this time, the maximum sintering pressure of 6 GPa is maintained for 7 minutes, and then naturally cooled to room temperature to obtain a BN-Al-ZrB2-TiC composite material.
[0074] Characterization and performance testing
[0075] Figure 1 is the XRD result of the BN-Al-ZrB2-TiC composite material in Example 2; Figure 1 It can be seen that ZrB2 reacts with TiC to generate TiB2, ZrC and (Zr,Ti)C.
[0076] Figure 2 is the SEM image of the sintered raw material after ball milling in Example 2; Figure 2 It can be seen that after the raw materials are ball-milled and mixed, they are evenly distributed without agglomeration.
[0077] Figure 3 Surface morphology of the BN-Al-ZrB2-TiC composite material prepared in Example 1; Figure 3 It can be seen that the binder is distributed and wrapped around the cBN particles.
[0078] Figure 4 This is a fracture morphology of the BN-Al-ZrB2-TiC composite material prepared in Example 2; Figure 4 It can be seen that the binder is densely combined with the cBN particles, and there are no defects such as pores inside the sintered body. When the sample breaks, there are transgranular fractures and intergranular fractures, but transgranular fractures are the main ones.
[0079] Figure 5 The flexural strength curve of the BN-Al-ZrB2-TiC composite material prepared in Example 3 was tested using the three-point bending method at a loading speed of 0.5 mm / min. Figure 5 It can be seen that as the cBN content in the sintered body gradually increases, the flexural strength shows a trend of first increasing and then decreasing; as the cBN content increases to a certain level, the binder content in the sintered body is low, and the cBN particles are mostly mechanically bonded, which causes the performance of the sintered body to decline.
[0080] Figure 6 The Vickers hardness curve of the BN-Al-ZrB2-TiC composite material prepared in Example 3 was tested by the indentation method with a loading load of 5 kN and a holding time of 15 s. Figure 6 It can be seen that as the cBN content in the sintered body gradually increases, the Vickers hardness shows an increasing trend. This is because the hardness of the sintered body is mainly determined by cBN, and as the cBN particles gradually increase, the hardness also gradually increases.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a BN-Al-ZrB2-TiC composite material, characterized in that: The following steps are involved: Performing a first mixing of zirconium boride and titanium carbide to obtain a first mixed material; The first mixed material is mixed with cubic boron nitride, aluminum powder and solvent for a second time, and then ball-milled, dried and sieved in sequence to obtain a second mixed material; The second mixed material is subjected to staged pressure sintering to obtain a BN-Al-ZrB2-TiC composite material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the zirconium boride to titanium carbide is 1:0.6-1.4, and the first mixing time is 15-45 minutes.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the cubic boron nitride, the aluminum powder and the first mixed material is 50-80:6:14-44.
4. The preparation method according to claim 1, characterized in that: The rotation speed of the ball mill is 80-200 r / min, the time is 360-840 min, and the ball-to-material ratio is 2-5:
1.
5. The preparation method according to claim 1, characterized in that: The drying temperature is 60-100° C., and the drying time is 16-30 hours; the mesh number of the sieve used for sieving is 100-400 meshes.
6. The preparation method according to claim 1, characterized in that: A six-sided top press is used to carry out the segmented pressure sintering; the pressure applied by the six-sided top press is 4 to 7 GPa.
7. The preparation method according to claim 1 or 6, characterized in that: The staged pressure sintering includes: the first stage: the temperature is 900-1400°C, the holding time is 1-3 minutes, and the heating rate from room temperature to the temperature of the first stage is 300-500°C / min; the second stage: the temperature is 1500-2000°C, the holding time is 5-10 minutes, and the heating rate from the temperature of the first stage to the temperature of the second stage is 300-500°C / min.
8. The BN-Al-ZrB2-TiC composite material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the BN-Al-ZrB2-TiC composite material according to claim 8 in a PcBN cutting tool.
Citation Information
Patent Citations
In-situ generated ZrB2-SiC toughened PcBN cutter and preparation method thereof
CN112500178A
Preparation method of boron nitride-spinel composite material
CN118561606A
pcbn cutting materials and processes for their manufacture
DE102015220389A1
Cubic system boron nitride base sintered body and its production
JP1994016476A
Cubic boron nitride sintered material
US20220267217A1